REVISITING MULTIMODAL DISCOURSE: A REVIEW OF INTRODUCING MULTIMODALITY (2ND EDITION, 2025) - Tran Hong Lam (Indonesian Journal of Linguistics, 2000)
This review examines the second edition of "Introducing Multimodality" (2025) by Jewitt, Bezemer, and O'Halloran. The book updates and refines several theoretical frameworks including Systemic Functional Linguistics, Social Semiotics, and Conversation Analysis. It also incorporates digital case studies and tools for conducting multimodal analysis. The review highlights the strengths of the book in terms of theoretical clarity and its usefulness for classroom teaching. At the same time, it points out some ongoing limitations, such as a lack of cultural inclusiveness and difficulties for beginner readers. Despite improvements in visual aids and methodological explanations, the book still mainly uses Western examples and academic terminology that may be difficult to access. Overall, this edition makes an important contribution to the study of multimodal discourse, especially for graduate-level instruction and research training.